(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the mechanisms of emotional regulation and interpreter neutrality in English–Russian diplomatic simultaneous interpreting, focusing on United Nations conference materials. Drawing upon psycholinguistic theories, the study examines how interpreters manage affective responses, cognitive load, and linguistic transfer while maintaining professional detachment. The research highlights that emotional control is not the absence of feeling, but the strategic regulation of empathy and cognitive focus during high-stakes discourse. Based on authentic UN speeches and interpretation transcripts, the analysis reveals recurrent strategies such as emotional distancing, cognitive reappraisal, and metacognitive monitoring. The findings demonstrate that interpreter neutrality is dynamically constructed through interactional and psycholinguistic mechanisms that ensure accuracy, impartiality, and emotional balance. This study contributes to a deeper understanding of the human factor in diplomatic interpreting and provides insights into interpreter training for emotionally charged, politically sensitive communicative settings.